Manipulation of plasmonic random laser from dye-doped liquid crystals inside photonic crystal fiber by the electric field. (July 2022) - Xie, Rui-Chen; Tsay, Shwu-Yun; Wu, Jin-Jei; Kuo, Chi-Ching; Zhang, Han; Lin, Ja-Hon
Highlights: Plasmonic random laser from photonic crystal fiber with NLCs and silver nanoprism. Performance enhancement of RLs and induce coherent feedback by applied voltage. White light scattering spectrum measurement to verify recurrent light scattering. Abstract: The manipulation of plasmonic random lasers (PRLs) from dye-doped liquid crystals (DDLCs) inside the air holes of photonic crystal fiber (PCF) with silver nanoprisms has been investigated by means of applied voltage. In comparison to the sample without AgNPs, PRL exhibits multiple emission spikes and a lower lasing threshold owing to the recurrent light scattering and the localized surface plasmon resonance (LSPR) effect. Through the modulation of the applied voltage above 80 V, the alignment of nematic liquid crystals inside the air holes of PCF will become more disordered to produce photon trapping for improving the output intensity of PRLs and will induce strong light scattering for turning the incoherent feedback to coherent feedback. When the applied voltage exceeds a certain value, the emission spike of RL does not increase further because of the gain saturation effect. The enhancement of light scattering inside the air holes of PCF as voltage increases was demonstrated by the white light scattering spectrum from polarization optical microscopy.